Health-Related Quality of Life, Family Climate and Sense of Coherence of Families in Which a Parent Has Deafblindness - Wahlqvist, Moa; Björk, Maria; Anderzén-Carlsson, Agneta; Huus, Karina (Frontiers in Education, 2020)
Introduction: The consequences of living with deafblindness can be vast and have been described as concerning difficulties with communication, restrictions in the activities of daily living and a lack of independence. Deafblindness has also been associated with poor health-related quality of life. Little is known about parenting when having deafblindness or how the health and family climate of families in which a parent has deafblindness are affected. Aim: The aim of the study was to describe the health-related quality of life, sense of coherence and family climate in families where a parent has a deafblindness. Methods: A total of 38 individuals, of which 14 were parents with deafblindness and 6 were partner to the parent with deafblindness, and 18 children, were included. The participants answered questionnaires about their health-related quality of life, family climate and sense of coherence (comprehensibility, manageability and meaningfulness). The Swedish age-relevant versions of the questionnaires were used. Due to the small number of participants, descriptive statistics were used to explore the results from the questionnaires. Results: The results revealed a pattern indicating that the health-related quality of life was affected, parents with deafblindness reported the poorest health-related quality of life. Sense of coherence was reported by all the family members as either moderate or low. The Family climate questionnaire revealed the positive aspect of closeness across family members, however negative aspects of chaos and expressiveness in the families were reported, mainly by, but not restricted to, the parent with deafblindness. Discussion: This study includes a small sample, too small to draw far-reaching conclusions. However, some interesting results need to be highlighted and discussed. When considering the family as a system, it is reasonable to assume that the family members contribute in different ways to how health and wellbeing is experienced in the family. Deafblindness is a unique disability that affects not only the individual but also the whole family. This fact needs to be considered when support is offered to individuals with deafblindness. All members of families where a parent has deafblindness have to be asked about their needs and about how they experience the situation.